2022
DOI: 10.25105/urbanenvirotech.v5i3.12776
|View full text |Cite
|
Sign up to set email alerts
|

Organic Removal in Domestic Wastewater Using Anaerobic Treatment System-MBBR With Flow Recirculation Ratio and Intermittent Aeration

Abstract: Aim: The modified Small-scale Domestic Sewage Treatment Plant (SDSTP) reactor with anaerobic fixed bed- aerobic Moving Bed Biofilm Reactor (MBBR) is implemented to find the optimum condition for organic degradation related to recirculation and intermittent aeration practices with the purpose to comply with the governmental regulation standard.  Methodology and Results: This research have been done with the artificial wastewater with characteristic similar to the sewage treatment plant (STP) of Telkom company w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Compared to a pseudo-second-order model, it can be shown why this model is inapplicable to the kinetics of ferrous cation adsorption onto kaolinite. Compared to the pseudo-firstorder model, the pseudo-second-order model more closely matches the experimental results [18]. Running kaolin with a reactor height of 20 cm produced the highest correlation coefficient (R 2 ) value of a pseudo-second-order model (R 2 = 0.9313).…”
Section: Modelling Of Adsorption Kinetic Datamentioning
confidence: 52%
“…Compared to a pseudo-second-order model, it can be shown why this model is inapplicable to the kinetics of ferrous cation adsorption onto kaolinite. Compared to the pseudo-firstorder model, the pseudo-second-order model more closely matches the experimental results [18]. Running kaolin with a reactor height of 20 cm produced the highest correlation coefficient (R 2 ) value of a pseudo-second-order model (R 2 = 0.9313).…”
Section: Modelling Of Adsorption Kinetic Datamentioning
confidence: 52%
“…The processes that may occur in organic materials removal when passing through the supporting media are filtration, adsorption, and biodegradation. In the filtration process, when water passes through the supporting media -acting as filter media -organic compounds will be retained, causing a decrease in COD concentration (Subroto et al, 2022). In the adsorption process, pollutants will enter the pores of the supporting media.…”
Section: Processes and Reactions That Possibly Occur In Cod Removal B...mentioning
confidence: 99%
“…Calculation in dry season Graph of COD degradation using MatLab application al., 2014;Zhang et al, 2018). The presence of oxygen causes the aerobic oxidation process to take place, organic materials will be converted into relatively stable final products and the rest will be synthesized into new microbes(Subroto et al, 2022). According toPrayogo et al (2020) andPrayogo et al (2023), biofilms on a supporting media usually take 30-40 days to grow optimally.…”
mentioning
confidence: 99%
“…Groundwater is recognized as a vital natural resource used by communities to satisfy their daily necessities. Subroto et al, (2022) reported that with the rising demand for clean water, there is an increase in the contamination of clean water due to various pollutants originating from diverse communal activities. Human activities require water, including personal hygiene, plant irrigation, and laundry.…”
Section: Introductionmentioning
confidence: 99%